Metavirome Sequencing of the Termite Gut Reveals the Presence of an Unexplored Bacteriophage Community - Tikhe, Chinmay V.; Husseneder, Claudia (Frontiers in Microbiology, 2018)
The Formosan subterranean termite; Coptotermes formosanus is nutritionally dependent on the complex and diverse community of bacteria and protozoa in their gut. Although, there have been many studies to decipher the taxonomic and functional diversity of bacterial community in the termite gut, their bacteriophages remain unstudied. In this study we sequenced the metavirome of the termite gut to study the diversity of bacteriophages and other associated viruses. Results showed that the termites harbor a diverse bacteriophage community in their gut. Taxonomically classifiable sequences from the virome, predominantly showed similarity to the tailed bacteriophages (Caudovirales). Many predicted genes from the virome matched to bacterial prophage regions. These data are suggestive of a virome dominated by temperate bacteriophages. We predicted the genomes of seven novel Caudovirales bacteriophages from the termite gut. Three of these predicted bacteriophage genomes were found in high proportions in all the three termite colonies tested. Two bacteriophages are predicted to infect endosymbiotic bacteria of the gut protozoa. The presence of these putative bacteriophages infecting endosymbionts of the gut protozoa, suggests a quadripartite relationship between the termites their symbiotic protozoa, endosymbiotic bacteria of the protozoa and their bacteriophages. Other than Caudovirales, ss-DNA virus related genes were also present in the termite gut. We predicted the genomes of 12 novel Microviridae phages from the termite gut and seven of which possibly represent a new proposed subfamily. Circovirus like genomes were also assembled from the termite gut at lower proportions. We predicted 10 novel circovirus genomes in this study. Whether these circoviruses infect the termites remains elusive at the moment. The functional and taxonomical annotations suggest that the termites may harbor a core virome comprised of the bacteriophages infecting endosymbionts of the gut protozoa.